Baveno VI and Expanded Baveno VI criteria successfully predicts the absence of high‐risk gastro‐oesophageal varices in a Chilean cohort. (22nd January 2020) - Gaete, María I.; Díaz, Luis A.; Arenas, Alex; González, Katherine; Cattaneo, Máximo; Fuster, Francisco; Henríquez, Romina; Soza, Alejandro; Arrese, Marco; Barrera, Francisco; Arab, Juan P.; Benítez, Carlos
Abstract: Background: Baveno VI and expanded Baveno VI criteria have been recommended to circumvent the need for endoscopy screening in patients with a very low probability of varices needing treatment (VNT). Aim: To validate these criteria in a Latin American population. Methods: The ability of Baveno VI criteria (liver stiffness measurement (LSM) <20 kPa and platelet count >150 × 103/μL) and expanded Baveno VI criteria (LSM < 25kPa and platelet count >110 × 103/μL) to exclude the presence of VNT was tested in a prospectively recruited cohort of patients with Child‐Pugh A liver cirrhosis and with no previous variceal haemorrhage who attended the liver clinics of three major hospitals in Chile. Results: Three hundred patients were included. The median (IQR) age was 61 [18‐86] years, median MELD was 8.0 (6‐17), median LSM was 17.2 (10.2‐77) kPa and median platelet count was 137 (23‐464) × 10 3 /μL. The main aetiology was non‐alcoholic fatty liver disease (67.3%). VNT were present in 18% of patients. The Baveno VI criteria had a sensitivity of 98.1% and a specificity of 38.2%, potentially sparing 31.3% of upper endoscopies with a very low risk of missing VNT (1.1%). The expanded Baveno VI criteria had a sensitivity of 90.7% and a specificity of 61%, potentially sparing 51.3% of upper endoscopies with a risk of missing VNT of 3.6%. Both criteria were independently associated with the absence of VNT. Conclusion: We validated the Baveno VI and expanded Baveno VI criteria in Chilean population, potentially sparing 31.3% and 51.3% of endoscopies, respectively, with a very low risk of missing VNT. Fondecyt 1191183.